2D Pb‐Halide Perovskites Can Self‐Heal Photodamage Better than 3D Ones. (11th March 2022) - Aharon, Sigalit; Ceratti, Davide Raffaele; Jasti, Naga Prathibha; Cremonesi, Llorenç; Feldman, Yishay; Potenza, Marco Alberto Carlo; Hodes, Gary; Cahen, David
Abstract: Adding a 2D character to halide perovskite (HaP) active layers in ambient‐protected cells can improve their stability drastically, which is not obvious from the hydrophobicity of the large cations that force the HaP into a 2D structure. Results of two‐photon confocal microscopy are reported to study inherent photo‐stability of 2D Pb iodide HaPs in the interior of single crystals. Compared to 3D HaP crystals, 2D ones have higher photo‐stability and, under a few sun‐equivalent conditions, self‐heal efficiently after photo‐damage. Using both photoluminescence (PL) intensities (as function of time after photo‐damage) and spectra, self‐healing dynamics of 2D HaP (C4 H9 NH3 )2 PbI4, 2D/3D (C4 H9 NH3 )2 (CH3 NH3 )2 Pb3 I10 and 3D MAPbI3 are compared. Differences in response to photo‐damage and self‐healing ability from different degrees of photo‐damage are found between these HaPs. Based on the findings, a possible chemical mechanism for photo‐damage and self‐healing of the 2D HaPs is suggested: the layered lattice arrangement limits out‐diffusion of degradation products, facilitating damage reversal, leading to better 2D HaP photo‐stability and self‐healing uniformity than for 2D/3D HaPs. One implication of the layered structures' resilience to photo‐damage is transfer of their increased stability to devices made with them, such as photovoltaic solar cells and light‐emitting diodes. Abstract : Degradation in 2D Pb‐iodide perovskites, induced by illumination of up to ≈5 suns equivalent, will self‐heal more completely or faster than in 3D ones. Better localization of degradation products in the layered structure, needed for degradation reversal, can explain this result.